Модернізація системи тропосферного зв'язку - Лошаков, В. А.; Мартинчук, О. О.; Москалець, М. В.; Білик, О. С.; Жуга, Ю. С.; Севрюков (ХНУРЕ, 2025)
The article considers the possibilities of modernizing the tropospheric communication system based on the use of SDR technologies and an unmanned repeater raised to a height of 200-400m. Such a system in emergency situations can become an adequate replacement for the low-orbit satellite communication system. Preliminary estimates indicate the possibility of practical implementation of cheap interference-protected direct high-speed communication lines with a range of up to 100-120 km.
Keywords: тропосферний зв'язок; tropospheric communication system